Analysis of main tasks and challenges in drone remote control - Sukhomlinova, D. A.; Sotnik, S. V. (ONUT Publishing House, 2025)
The study conducts a comprehensive analysis of the main tasks and challenges in remote drone control within military, civilian, and commercial sectors. It systematizes the functional tasks of drones and structures organizational challenges by application areas, including regulatory frameworks for air traffic, cybersecurity protection, logistics optimization, and multi-drone fleet management. Technical challenges are classified into four categories: ensuring stable communication, power supply, navigation, and automation of control. The potential of artificial intelligence methods for addressing technical problems is analyzed, particularly the application of CNNs for obstacle detection, DRL for trajectory optimization, Edge AI for latency reduction, and Swarm Intelligence for group coordination. Promising research directions are identified, including adaptive swarm control, quantum-resistant encryption, and the integration of 5G/6G technologies.
Аналіз основних завдань та викликів у дистанційному керуванні дронами
Дослідження проводить комплексний аналіз основних завдань і викликів у віддаленому керуванні дронами у військовому, цивільному та комерційному секторах. Систематизовано функціональні завдання дронів та структуровано організаційні виклики за сферами застосування, включаючи нормативні рамки повітряного руху, захист кібербезпеки, оптимізацію логістики та управління флотом багатьох дронів. Технічні виклики класифіковані на чотири категорії: забезпечення стабільного зв’язку, енергопостачання, навігації та автоматизації управління. Проаналізовано потенціал методів штучного інтелекту для вирішення технічних проблем, зокрема застосування CNN для виявлення перешкод, DRL для оптимізації траєкторії, Edge AI для зменшення затримки та Swarm Intelligence для координації групи. Визначено перспективні напрями досліджень, включаючи адаптивне управління роями, квантово-стійке шифрування та інтеграцію технологій 5G/6G.
Keywords: Unmanned aerial vehicles (UAVs); БПЛА; дистанційне керування; згуртований інтелект; квантово-стійке шифрування; технології 5G/6G